Personal Emotions, Experiences and Attacks: Immigration Debate in Scandinavian Comment Sections. Issue 2 (3rd April 2019) - Andersen, Ida
Abstract : The public sphere is where citizens can come together to discuss issues of public concern and attempt to influence the political handling of these. Social media and online discussion forums have created new arenas where citizens can participate in the public debate. Discussions found in these arenas, however, seldom hold deliberative qualities. This paper examines how one increasingly complex and controversial issue – immigration – is discussed in Scandinavian newspapers' comment sections. It does so through a case study of discussions about the arrival of Syrian refugees to the three nation-states. Rather than evaluating the deliberative functions of these discussions, the paper asks how the rhetorical situation influences how attitudes are expressed, and how these utterances in turn function in the particular situation. The analysis finds that similar rhetorical practices are performed independent of the national context, suggesting that the individual speaker's rhetorical latitude is contingent upon the issue and the arena. The ways in which these practices are performed, however, differ between the three national contexts, suggesting that the cultural context in which the discussion takes place also influences the individual speaker's rhetorical latitude.